Quincke’s disease, a rare clinical disorder: a case report - Zikry Gifari (Universa Medicina)
Background Quincke's disease, or isolated uvular angioedema, is a rare clinical condition and reports on its etiology and management remain limited. Most cases are linked to idiopathic conditions, food allergies, airborne allergens, medications (ACE inhibitors, NSAIDs), hereditary angioneurotic edema, oropharyngeal trauma, and infections. The disease may be encountered in any emergency setup and must be dealt with rapidly and with utmost vigilance to prevent progression and complications.